Histiocytic necrotising lymphadenitis (Kikuchi-Fujimoto disease) of axillary lymph nodes. (5th January 2015) - Nagaraju, Santosh; Vaishnav, Sakshi; Burke, Leandra H; Norman, Earl M
Abstract : Kikuchi-Fujimoto disease (KFD) or histiocytic necrotising lymphadenitis is a rare entity, occurring most commonly in young Asian adults. KFD is characterised by fever with tender lymph node enlargement. The cervical group of lymph nodes is most commonly involved, and the diagnosis is conclusively made by lymph node biopsy and histopathology. KFD is a self-limiting condition, which usually resolves over 1–4 months. Symptomatic treatment with antipyretics and/or non-steroidal anti-inflammatory drugs is recommended. Here we describe an uncommon presentation of KFD in a young woman in which only the axillary lymph nodes were enlarged.